A Normal Preoperative Lipase Serum Level Is an Easy and Objective Risk Factor of Pancreatic Fistula After Pancreaticoduodenectomy. Issue 9 (October 2017) - Gagnière, Johan; Abjean, Adeline; Franz, Martin; Aumont, Ophélie; Pereira, Bruno; Dupré, Aurélien; Veziant, Julie; Le Roy, Bertrand; Boyer, Louis; Pezet, Denis; Buc, Emmanuel
Abstract : Objectives: The evaluation of the risk of postoperative pancreatic fistula (POPF) after pancreaticoduodenectomy is crucial to optimize perioperative strategies. Many risk factors of POPF have been identified and were included in scores. Performances of these scores have to be improved because of the use of subjective and/or intraoperative factors. We tried to identify new risk factors of POPF that could improve the performance of validated scores. Methods: We analyzed data from a prospective database of 191 consecutive patients who underwent a pancreaticoduodenectomy. Recorded data included a comprehensive inventory of pre-, intra- and postoperative clinical, biological and radiological data. Results: The rate of POPF was significantly increased in patients with a normal preoperative lipase serum level (LSL) (29.8% vs 6.8%; P = 0.001). After multivariate analysis, a normal preoperative LSL was a strong independent risk factor of both POPF (odds ratio, 7.06; P = 0.001) and clinically relevant POPF (odds ratio, 3.11; P = 0.036). The addition of the normality of the preoperative LSL to the Fistula Risk Score significantly improved its performance ( P < 0.001). Conclusions: A normal preoperative LSL was a strong, easy, and objective preoperative risk factor of POPF. Its addition to the Fistula Risk Score improved its performance and allows a more accurate evaluation of the risk of POPF.